On heat and moisture transfer characteristics of a desiccant dehumidification unit using fin tube heat exchanger with silica gel coating. (5th December 2015) - Zhao, Y.; Dai, Y.J.; Ge, T.S.; Sun, X.Y.; Wang, R.Z.
Abstract: In this paper, the heat and moisture transfer characteristics of a desiccant dehumidification unit using fin-tube heat exchanger with silica gel coating have been experimentally investigated. The present study focuses on the analysis of air side heat and moisture transfer performance in dehumidification mode. The empirical formula on Nusselt and Sherwood numbers were deducted and curve fitted from the test results under various operation conditions, using the non-linear least square method. The typical operation condition is that the air side Reynolds number ranges between 220 and 550 and tube side cooling water flow rate is about 7.7 L/min. Further tests indicate that the correlations of Nusselt and Sherwood number on air side of the unit agree well with the test results, and the mean errors are about ±10% and ±12%, respectively. Finally, the improvements of the operation and configuration parameters of this novel heat and moisture transfer components are discussed with those formulas. It is found that the correlated formulas provide the theoretical basis and practical experience for design and optimization of the desiccant dehumidification unit using fin tube heat exchanger with silica gel coating. Highlights: On the basis of experimental results, we analyze the heat and moisture transfer performance of SCHE. The empirical formula on Nu and Sh of SCHE are deducted using L–M method. Using those formulas, we can predict the results in terms of heat and moisture transfer performance of SCHE.